Kína geopolitikai viszonyai a harmonikus világrend elmélet tükrében - Boros, Szilárd (Közép-Európai Közlemények, 2017)
In the last decade China has made several economic and diplomatic effort to alter its surrounding international relation system, which was not in accordance with its economic strength at millenium. The paper on the one hand examines the chinese cultural background of harmonised world order theory elaborated by the Chinese school of international relations, on the other hand the practical geopolitical impementation through the dimensions of Chinese multilater policy and the One Belt One Road (OBOR) plan. The first part of the paper draws up briefy the main caracteristics of the development of China’s international reations in the 20th century foucusing on the harmonised world order. The second part unfolds the main Chinese cultural aspects and elements of the theory and compaire them to some Western ones. The last part of the paper examines the practial implementation of the theory in two fields, namely the Chinese multilater policy and OBOR. The concluding chapter summarizes the main findings of the paper and make suggestions for further subjects of inquery.